Penguatan Kelompok Tani Berbasis Produksi dan Agrowisata Kopi di Kecamatan Way Ratai, Kabupaten Pesawaran, Lampung - Evizal Rusdi; Fembriarti Erry Prasmatiwi; Sarno Sarno; Otik Nawansih; Dedy Miswar; Liska Mutiara Septiana (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Lampung Province is the center of Robusta coffee production while Arabica coffee has begun to be developed in the area, including in Harapan Jaya Village, Way Ratai Subdistrict, District of Pesawaran. This village is an ecotourism destination and also has a potential of agrotourism, especially Arabica coffee farming. The objectives of the Community Service Activities are: 1) Increasing knowledge and skills of farmer group members in Arabica coffee agrotechnology; 2) increasing coffee plantation productivity through proper maintenance; and 3) Formulating a model of strengthening farmer group based on coffee agrotourism. This program was carried out at the Karya Subur Farmer Group, in Harapan Jaya Village in year 2018–2019. The methods used are discourse, training, demonstration plots, mentoring, and discussion. The results of this program conclude that: 1) Increasing the knowledge and skills of farmer group members in Arabica coffee agrotechnology; 2) Increasing productivity of coffee plantations plot belonging to the group members assisted; and 3) a model of strengthening of farmer groups based on coffee production and agrotourism is through increasing group capacity in tourism and tourism activities related to the coffee production process from upstream to downstream, increasing accessibility and facilities coordinated with village officials, and increasing agro tourism promotion especially to educational institutions, professionals, and communities.